The green fuse [videorecording] - Abadilla, Domingo C.; Patolot, Mike; Trofeo, Dick (The Philippine Futuristics Society, [production company] ; Makati : Felta Book Sales, [distributor], 1990)
Summary: Focuses on forest conservation and environmental protection. Shows some of the forest that are denuded and the factors that causes their destruction such as illegal logging.